1954
DOI: 10.1017/s0021859600045809
|View full text |Cite
|
Sign up to set email alerts
|

Studies in grazing behaviour of dairy cattle: II. Bloat in relation to grazing behaviour

Abstract: 1. Four trials on methods of bloat-prevention vare described: (a) A comparison of ‘break’ grazing and normal ‘rotational’ grazing without restriction of feed in either case. Break grazing observations covered two and five breaks per day.(b) A comparison of these two systems where ‘break’ grazing involved restriction of area available to the cows, and ‘breaks’ varied from seven to eleven per day.(c) Comparison of ‘off and on’ grazing with normal rotational methods in an attempt to force changes in grazing patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1966
1966
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…However, there has been little formal experimentation on the effect of feeding schedule on the incidence of bloat. We are not aware ofany published reports between 1954 (Hancock 1954) and1990 (Hall and Majak 1990). In the latter study we found that animals fed freshly harvested alfalfa twice a day (30 kg at 0830 h, 20 kg at 1400 h) bloated more than when they were offered the same total amount of feed once a day at 0830 h. When bloat occurred, it was observed only after the morning feeding.…”
mentioning
confidence: 71%
“…However, there has been little formal experimentation on the effect of feeding schedule on the incidence of bloat. We are not aware ofany published reports between 1954 (Hancock 1954) and1990 (Hall and Majak 1990). In the latter study we found that animals fed freshly harvested alfalfa twice a day (30 kg at 0830 h, 20 kg at 1400 h) bloated more than when they were offered the same total amount of feed once a day at 0830 h. When bloat occurred, it was observed only after the morning feeding.…”
mentioning
confidence: 71%
“…Eructation and feeding behaviours are modified as the rumen's static pressure increases, to adjust to the new gas dynamics (Cole et al 1945). Grazing bouts are shorter, rumination times are reduced and ruminal movements increase in frequency (Hancock 1954). Production losses are primarily a result of a reduced feed intake (Johns 1954;Reid and Johns 1957;Alder et al 1967;Hall et al 1988).…”
Section: Types Of Bloatmentioning
confidence: 99%
“…Input and output from the rumen can be indirectly affected by adopting grazing and feeding regimens that increase rumen clearance, or reduce gas and foam production. Control is a function of the rancher's skill at managing the interaction between availability and digestibility of pastured forage and the grazing behaviour of the animals (Hancock 1954;Allison 1985;Hall et al 1994b;Majak et al 1995).…”
Section: Prevention and Control Of Frothy Bloatmentioning
confidence: 99%
“…The importance of heredity in accounting for variations in individual susceptibility has been reported in papers re viewed by Huffman , in identical twin studies conducted by Hancock (1954) and by Johns (1954) and other studies reviewed by Johns (1956a). Some mechanisms prob ably affected by heredity and related to bloat are differences in composition of the saliva , differences in the efficiency of eructation (Huffman, in Cole et.…”
Section: Foam Theorymentioning
confidence: 90%
“…Alteration of the grazing, pattern Hancock's (1954) trials with identical twins are classics in this area. He found that strip grazing, with or without restrictions of in take, gave no effective control of bloat.…”
Section: Grazing Controlmentioning
confidence: 99%